Investigation of electrostatically tunable adhesion and instability of flying head slider - Fan Zhang; Yu Wang; Yueqiang Hu; Mingquan Zhang; Baotong Li (Friction)
Abstract The interfacial adhesion between microstructures is inevitable in a micro-electro-mechanical system (e.g., hard disk drive (HDD)), which may lead to complicated microtribodynamics problems. This research has investigated the effect of surface potential on the interfacial adhesion and microtribodynamics of the head–disk interface (HDI) in an HDD. A dynamic continuum surface force model, where the electrowetting is considered, is proposed to evaluate the interfacial interaction, and then employed into a two-degree-of-freedom (2DOF) model to theoretically analyze the potential influence mechanism on the microtribodynamics. The results confirm that the elimination of potential can effectively repress the adhesion retention, which is further proved by the measured slider response with a laser Doppler vibrometer (LDV). Moreover, the effect of the potential on the adhesion-induced instability is also analyzed through the phase portrait. It tells that the critical stable flying height can be lowered with the elimination of potential.